The Effect of Compensation, Work Environment and Leadership on Job Satisfaction - Ardini, Wahyunita Putri; Ariani, Misna; Arrywibowo, Imam (Universitas Syiah Kuala, 2025)
The purpose of this study is to determine the effect of Compensation , Work Environment and Leadership on Employee Job Satisfaction at PT PLN UP3 Balikpapa. In this study, there was a population of 71 company employees and a sample of 53 respondents . The method used in this study was a statistical test with primary data . from the distributed questionnaire . Data analysis using SmarPLS. The results of the study showed that partially the variables of compensation, work environment and leadership had a positive effect on employee job satisfaction.